Effect of temporomandibular joint anterior disc displacement on condylar height in different age groups - Siyu Wu; Dahe Zhang; Simo Xia; Pei Shen; Chi Yang (BMC Oral Health)
Abstract Background Temporomandibular joint ADD is highly prevalent and harmful, and some patients have no obvious clinical symptoms, but it can cause facial asymmetry, mandibular retrusion and other dental and maxillofacial deformities. Nevertheless, the impact of ADD on condylar height in individuals of varying age groups remains uncertain particularly with regard to condylar heights at different stages of development. The aim of this retrospective case-control study was to investigate the association between condylar height and temporomandibular joint anterior disc displacement (ADD) in different age groups. Materials and methods Patient characteristics, condylar height, disc length, and displacement distance at the baseline (T0) and the second follow-up visit (T1) were collected, and the differences between the two-time points were analyzed. Results A total of 149 patients who were diagnosed with unilateral ADD were included in the study. In comparison to T0, the affected condylar height decreased 0.66 mm, whereas the non-affected condylar height increased 1.37 mm at T1. The further subgroup analysis revealed no statistically significant change in the affected condylar height of the 11–17 age group. However, a considerable reduction in height was observed on the ADD side in the subgroup above 18 years, when compared to the T0 period. Conclusions ADD disrupts the normal development of condylar bone and cartilage in all age groups. Clinician recognises that ADD results in condylar height inhibition in the young and condylar height reduction in the adult.